IMPLEMENTASI MODEL MEANINGFUL INTRUCTIONAL DESIGN: MANFAATNYA TERHADAP KEMAMPUAN REPRESENTASI DAN KONEKSI MATEMATIS - Sri Purwanti Nasution; Fredi Ganda Putra; Via Anisa Putri; Riyama Ambarwati; Nurhasanah Leni (FKIP Universitas Sultan Ageng Tirtayasa, 2024)
ABSTRAKKemampuan representasi adalah proses berpikir dalam menginterprestasikan suatu masalah dalam bentuk gambar, simbol, angka dan kalimat. Sedangkan kemampuan koneksi matematis berkaitan dengan kemampuan peserta didik dalam menghubungkan antar konsep matematika. Penelitian ini bertujuan untuk Apakah terdapat pengaruh model pembelajaran Meaningful Intructional Design terhadap kemampuan representasi dan kemampuan koneksi matematis peserta didik, Apakah terdapat pengaruh model pembelajaran Meaningful Intructional terhadap kemampuan representasi peserta didik dan Apakah terdapat pengaruh model pembelajaran Meaningful Intructional Design terhadap kemampuan koneksi matematis peserta didik. Penelitian ini berjenis kuantitatif yang mengkaji kemampuan representasi dan kemampuan koneksi matematis peserta didik dengan menerapakan model Meaningful Intructional Design. Partisipan dalam penelitian ini berjumlah 60 peserta didik SMP, dengan rincian 30 peserta didik belajar menggunakan model Meaningful Intructional Design dan 30 peserta didik belajar dengan model konvensional. Alat yang digunakan untuk mengumpulkan data adalah tes dan dokumentasi. Uji hipotesis yang digunakan adalah MANOVA (Multifariate analisis of varian). Hasil uji hipotesis menunjukkan terdapat pengaruh model pembelajaran Meaningful Intructional Design terhadap kemampuan representasi dan kemampuan koneksi matematis peserta didik, terdapat pengaruh model pembelajaran Meaningful Intructional Design terhadap kemampuan representasi peserta didik dan terdapat pengaruh model pembelajaran Meaningful Intructional Design terhadap kemampuan koneksi matematis peserta didik Kata Kunci: Meaningful Intructional Design; kemampuan representasi dan koneksi matematis ABSTRACTRepresentation ability is a thinking process in interpreting a problem in the form of images, symbols, numbers and sentences. Meanwhile, mathematical connection ability is related to students' ability to connect mathematical concepts. This research aims to determine whether there is an influence of the Meaningful Instructional Design learning model on students' mathematical representation and connection abilities, whether there is an influence of the Meaningful Instructional learning model on students' representation abilities and whether there is an influence of the Meaningful Instructional Design learning model on students' mathematical connection abilities. This research is a quantitative type that examines students' mathematical representation and connection abilities by applying the Meaningful Instructional Design model. The participants in this research were 60 junior high school students, with details of 30 students studying using the Meaningful Instructional Design model and 30 students studying using the conventional model. The tools used to collect data are tests and documentation. The hypothesis test used is MANOVA (Multifariate analysis of variance). The results of the hypothesis test show that there is an influence of the Meaningful Instructional Design learning model on students' representation abilities and mathematical connection abilities, there is an influence of the Meaningful Instructional Design learning model on students' representation abilities and there is an influence of the Meaningful Instructional Design learning model on students' mathematical connection abilities. Keywords: Meaningful Instructional Design; mathematical representation and connection abilities